INTEGRASI BERPIKIR ALGORITMIK DALAM STRATEGI PEMBELAJARAN LITERASI ICT DI PENDIDIKAN TINGGI - Dwikalsum, Dwikalsum; Yahfizham, Yahfizham (ADIDAYA : Aplikasi Pendidikan dan Sosial Budaya, 2025)
In the digital era, Information and Communication Technology (ICT) literacy is an important skill that students must have in order to adapt to technological developments. This literacy not only includes the ability to use digital devices, but also the ability to think critically, logically, and systematically. One relevant approach to support the development of ICT literacy is algorithmic thinking. This research seeks to elaborate on how the integration of algorithmic thinking in the Information and Communication Technology (ICT) literacy learning strategy in higher education. A qualitative approach was applied using literature-based research as the primary method descriptive approach to various sources of scientific literature. The results of the study show that algorithmic thinking can improve students' abilities in solving digital problems, analyzing data, and designing solutions logically. This integration also helps students understand technology in depth and become reflective users. However, challenges remain, such as curriculum limitations and minimal lecturer training. Therefore, an interdisciplinary learning strategy is needed that encourages the development of a structured mindset in strengthening Information and Communication Technology (ICT) literacy.